The march of the jews - Burtis, Francis Charles (My University, 1891)
Introduction: Some judge the grandeur of a nation by the extent of its dominion and the number of its great castles, but this is not an infallible test of greatness for history shows us that such nations are not always the greatest nor do they leave the greatest effect upon the world. In the southwestern corner of Syria, is a country small in extent, not over one-hundred and fifty miles long and fifty miles wide known as Palestine, the home of the Hebrews, or Jews. Of all the nations of the world this nation has the most wonderful history. From the earliest time to the Christian era, it may be traced like the course of a mighty river. Even there, when their national existence is broken up, they are not lost among the nations, but still are like the River which keeps the color if its waters far out upon the open sea. As a writer says, “When little more numerous than a family, they had their language, customs and peculiar observances, treated with princes, and in every respect acted as a nation.
Citation: Burtis, Francis Charles. The march of the jews. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Palestine; Judaism; History; Theses; Manuscripts (documents)